Coastal plastic pollution monitoring in Iceland - Laureen Burlat 1994- (2022)
Plastic pollution has drastically increased in the world’s oceans since the mid-20th century due to poor waste management and irresponsible production. About 15% of all marine debris end-up in coastal areas, while the percentage of plastic among them range from 60% to 95%. In Iceland, six non-governmental organizations and the Environment Agency clean and monitor plastic on beaches across the country. However, there is no national database on coastal plastic pollution or coordinated data collection guidelines. This mixed methods study explores the issue of coastal plastic pollution in the Icelandic context and how it is managed. The quantitative component of the study focuses on monitoring one site in the Snæfellsnes peninsula with a seasonal accumulation survey for one year. The qualitative component investigates what is being done by environmental organizations and the Icelandic government through a series of interviews. The results show that 78.5% of all debris retrieved from the surveyed shore were plastics. Beach wracks were found to be strongly correlated with the quantities of plastic debris entering coastal environments (R2>0.9; p<0.0002), which helps explain daily and seasonal variations in debris quantities. The interviews demonstrated an overall focus on cleaning rather than collecting data in Iceland. Poor coordination, a lack of resources, and insufficient communication between environmental organizations were identified as the main barriers to establishing a coherent database. Guidelines for both beach monitoring and beach clean-ups are proposed, to support the collection of consistent data and promote the systematic publication of findings to inform advocacy and awareness raising. Plastmengun hefur stóraukist í höfum heimsins síðan um miðja síðustu öld vegna slæmrar meðhöndlunar úrgangs og ábyrgðarlausra framleiðsluhátta. Um 15% af öllu rusli í sjónum berst á strandir og er 60% - 95% af því plast. Á Íslandi eru það sex frjáls félagasamtök ásamt Umhverfisstofnun sem hreinsa og fylgjast með ...